Bacteriocins, Potent Antimicrobial Peptides and the Fight against Multi Drug Resistant Species: Resistance Is Futile? - Elaine Meade; Mark Anthony Slattery; Mary Garvey (MDPI AG, 2020)
Despite highly specialized international interventions and policies in place today, the rapid emergence and dissemination of resistant bacterial species continue to occur globally, threatening the longevity of antibiotics in the medical sector. In particular, problematic nosocomial infections caused by multidrug resistant Gram-negative pathogens present as a major burden to both patients and healthcare systems, with annual mortality rates incrementally rising. Bacteriocins, peptidic toxins produced by bacteria, offer promising potential as substitutes or conjugates to current therapeutic compounds. These non-toxic peptides exhibit significant potency against certain bacteria (including multidrug-resistant species), while producer strains remain insusceptible to the bactericidal peptides. The selectivity and safety profile of bacteriocins have been highlighted as superior advantages over traditional antibiotics; however, many aspects regarding their efficacy are still unknown. Although active at low concentrations, bacteriocins typically have low in vivo stability, being susceptible to degradation by proteolytic enzymes. Another major drawback lies in the feasibility of large-scale production, with these key features collectively limiting their current clinical application. Though such limitations require extensive research, the concept of expanding bacteriocins from food preservation to human health opens many fascinating doors, including novel drug delivery systems and anticancer treatment applications.